Novel Probable Glance at Inflammatory Scenario Development in Autistic Pathology - Harutyunyan, Aida A.; Harutyunyan, Hayk A.; Yenkoyan, Konstantin B. (Frontiers in Psychiatry, 2021)
Autism Spectrum Disorder (ASD) is characterized by persistent deficits in social communication, and restricted-repetitive patterns of behavior, interests, or activities. ASD is generally associated with chronic inflammatory states, which are linked to immune system dysfunction and/or hyperactivation. The latter might be considered as one of the factors damaging neuronal cells. Several cell types trigger and sustain such neuroinflammation. In this study, we traced different markers of immune system activation on both cellular (immune cell phenotypes) and mediatory levels (production of cytokines) alongside adverse hematology and biochemistry screening in a group of autistic children. In addition, we analyzed the main metabolic pathways potentially involved in ASD development: energy (citric acid cycle components), porphyrin and neurotransmitter metabolism. Several ASD etiological factors like heavy metal intoxication and risk factors – genetic polymorphisms of the relevant neurotransmitters and vitamin D receptors were also analyzed. Finally, broad linear regression analysis allowed us to elucidate the possible scenario that led to the development of chronic inflammation in ASD patients. Obtained data showed elevated levels of urinary cis-aconitate, isocitrate, alfa-ketoglutarate, and HMG. There were no changes in levels of metabolites of monoamine neurotransmitters, however, the liver-specific tryptophan kinurenine pathway metabolites showed increased levels of quinolinate (QUIN) and picolinate, whereas the level of kynurenate remained unchanged. Abovementioned data testify the infringement in energy metabolism. We found elevated level of lead in red blood cells, as well as altered porphyrin metabolism, which support etiological role of heavy metal intoxication in ASD. Lead intoxication, the effect of which is intensified by a mutation of the VDR-Taq and MAO-A leads to quinolinic acid increase, resulting in energy metabolism depletion and mitochondrial dysfunction. Moreover, our data backing the CD4+CD3+ T-cell dependence of mitochondrial dysfunction development in ASD patient reported in our previous study. We come to the conclusion that redox-immune cross-talk is considered a main functional cell damaging factor in ASD patients.